The Influence of Social Media Marketing, Coffee House Brand Experience, Brand Equity and Customer Relationship on Repurchase Intention on Janji Jiwa - Andarina, Feby; Ariyanti, Maya (International Journal of Science, Technology & Management, 2026)
The coffee shop industry in Indonesia is experiencing rapid growth, driven by lifestyle changes and increasing domestic coffee consumption. Janji Jiwa, as one of the leading local coffee brands, faces challenges in maintaining consumer loyalty amid intense market competition. This study aims to examine the influence of Social Media Marketing, Coffee House Brand Experience, Brand Equity, and Customer Relationship on the Repurchase Intention of Janji Jiwa consumers, particularly through the Instagram platform. A quantitative research method was employed, with data analyzed using PLS-SEM. Data were collected through questionnaires distributed to active Janji Jiwa customers. The results indicate that Social Media Marketing has a significant positive influence on both Brand Equity and Customer Relationship, which ultimately affect Repurchase Intention. However, the variable Coffee House Brand Experience does not have a significant impact on Repurchase Intention for Janji Jiwa. This research contributes to a deeper understanding of the importance of integrating digital marketing strategies with brand experience and customer relationships in enhancing consumer loyalty.